2015
DOI: 10.2169/internalmedicine.54.3747
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cerebral Lobar Microbleeds and a Decreased Cerebral Blood Flow in a Memory Clinic Setting

Abstract: Objective Cerebral microbleeds (MBs) have been previously associated with cognitive dysfunction, including Alzheimer's disease. In the present study, we aimed to clarify the relationship between cerebral lobar MBs and the regional cerebral blood flow (CBF). Methods We investigated the data obtained from 122 patients in our memory clinic who were examined by both MRI and 99m Tc-ethyl cysteinate dimer (ECD)-single photon emission computed tomography (SPECT). Patient brain scans were superimposed and brain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In DPA, cerebral CMB are commonly found in the deep grey (Bg, thalami) and white matter, and infratentorially (brainstem, cerebellum) (Figure B ) . A strictly lobar (cortico‐subcortical) pattern of CMB (typically located most often in the occipital and temporal cortical grey matter) has high specificity for CAA (Figure B ) . The burden of CAA‐related lobar CMB seems to be associated with cortical position emission tomography (PET) Aβ load , but a recent analysis questioned the common expectation that in CAA, the ruptured vessel displays significant Aβ load, as microhaemorrhages were preferentially found surrounding the Aβ negative small vasculature .…”
Section: Neuroimaging Biomarkers Of Sporadic Csvdmentioning
confidence: 99%
“…In DPA, cerebral CMB are commonly found in the deep grey (Bg, thalami) and white matter, and infratentorially (brainstem, cerebellum) (Figure B ) . A strictly lobar (cortico‐subcortical) pattern of CMB (typically located most often in the occipital and temporal cortical grey matter) has high specificity for CAA (Figure B ) . The burden of CAA‐related lobar CMB seems to be associated with cortical position emission tomography (PET) Aβ load , but a recent analysis questioned the common expectation that in CAA, the ruptured vessel displays significant Aβ load, as microhaemorrhages were preferentially found surrounding the Aβ negative small vasculature .…”
Section: Neuroimaging Biomarkers Of Sporadic Csvdmentioning
confidence: 99%
“…Similarly, in patients with ischemic stroke and/or transient ischemic attacks, lobar CMBs are associated with executive dysfunction[25]. Lobar CMBs are also associated with lower cerebral blood flow and hypoperfusion in both healthy elderly and in a memory clinic setting [26,27], which highlights the complex interaction of SVD with healthy ageing. Again, ApoE ε4 is associated with lobar CMBs in patients with cognitive impairment[28].…”
Section: Vascular Factors In Admentioning
confidence: 99%
“…It is further reported that lobar CMBs may alter cerebral white matter perfusion leading to brain volume reduction [11, 12]. However, previous studies have shown conflicting results.…”
Section: Introductionmentioning
confidence: 99%